2012
DOI: 10.1590/s2237-93632012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological evaluation of patients with colorectal cancer from Rio Grande do Sul

Abstract: Colorectal cancer has a high incidence in Brazil, with the South and Southeast regions presenting the largest number of cases. OBJECTIVE: Identify the epidemiological characteristics and the regimens used as first-line treatment of patients with colorectal cancer treated at a cancer center in Santa Cruz do Sul (RS, Brazil) from 2006 to 2011. METHODS: The records of 130 patients were retrospectively evaluated. Clinical and epidemiological characteristics, such as age, gender, ethnic group, stage of disease, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In Brazil, there is a high incidence in the South and Southeast regions, especially in older individuals and in males. 7 In this study, the mean age was 56 years, which is in line with the literature findings. 8,9 The exact cause of CRC is unknown, but there is strong involvement of genetic and environmental characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…In Brazil, there is a high incidence in the South and Southeast regions, especially in older individuals and in males. 7 In this study, the mean age was 56 years, which is in line with the literature findings. 8,9 The exact cause of CRC is unknown, but there is strong involvement of genetic and environmental characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…1 In the Northern region of Portugal, it is the second most common neoplasm. 2 The clinical-pathological characteristics of the present sample were similar to those described in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] ; CRC is more frequent in men 11,15,16 and in those aged over 45 years. 11,[17][18][19][20][21] In fact, CRC is often defined as a disease of the elderly; advanced age is a risk factor for this neoplasm.…”
Section: Discussion/conclusionsupporting
confidence: 67%
“…Regarding tumor differentiation, in the present sample 50% of the CRC were well differentiated, in agreement with other studies. [27][28][29] VO was present in 89.7% of patients, a figure higher than that reported by Park et al 6 The only relationship observed was between VO and male sex (p = 0.032), a finding not previously described. 6…”
Section: Survival Functionmentioning
confidence: 84%